2000
DOI: 10.1046/j.1365-2605.2000.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality over a 10‐year period in 22,249 men in Korea

Abstract: A retrospective study was conducted in a large population presenting with infertility to determine whether sperm quality has changed in Korea in the last 10 years. We reviewed sperm concentration, motility and semen volume in 22,249 men from whom semen was collected in our laboratory between January 1989 and April 1998 and analysed according to WHO (1987) guidelines. Mean age of the men was 32 years (range 21-40). Data were collected in healthy men with infertility. The mean sperm concentration was 60.5 x 10(6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…For example, Tortolero et al (1999) reported on a longitudinal investigation of Venezuelan men in which sperm counts remained well within the range of clinical acceptability with little or no change over a period of 15 years. An extensive study of sperm count and quality in Korean men over a span of 10 years also yielded similar results, although 19% of the men exhibited azoospermia, suggesting that male subfecundity merits further investigation in this population (Seo et al, 2000). Results from Europe also fail to document any significant longitudinal changes in sperm quality or count (Andolz et al, 1999;Berling and Wolner-Hanssen, 1997;Rasmussen et al, 1997).…”
Section: Sperm Countmentioning
confidence: 81%
“…For example, Tortolero et al (1999) reported on a longitudinal investigation of Venezuelan men in which sperm counts remained well within the range of clinical acceptability with little or no change over a period of 15 years. An extensive study of sperm count and quality in Korean men over a span of 10 years also yielded similar results, although 19% of the men exhibited azoospermia, suggesting that male subfecundity merits further investigation in this population (Seo et al, 2000). Results from Europe also fail to document any significant longitudinal changes in sperm quality or count (Andolz et al, 1999;Berling and Wolner-Hanssen, 1997;Rasmussen et al, 1997).…”
Section: Sperm Countmentioning
confidence: 81%
“…Studies from Italy, Denmark, Canada, Tunisia, India, Poland, Israel, Scotland, Greece and Germany suggest that there has been a decline, or sperm parameters are impaired in young populations (Adamopoulos et al, 1996;Younglai et al, 1998;Bilotta et al, 1999;Almagor et al, 2003;Vicari et al, 2003;Jørgensen et al, 2006;Sripada et al, 2007;Adiga et al, 2008;Paasch et al, 2008;Horak et al, 2008;Feki et al, 2009). Conversely, other reports from US, Japan, Korea, Sweden, Spain, Israel and Czech Republic showed no significant evidence of deterioration in sperm quality (Fisch et al, 1996;Paulsen et al, 1996;Benshushan et al, 1997;Berling & Wölner-Hanssen, 1997;Andolz et al, 1999;Seo et al, 2000;Itoh et al, 2001;Zvĕrina et al, 2002). The materials and methods of the studies mentioned varied widely, as well as time period (one, two, or more decades), population sample (e.g.…”
Section: Pesticides and Semen Qualitymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] By contrast, other studies have shown no evidence of deteriorating semen quality. [9][10][11][12][13][14][15][16] Some studies concern infertile couples, while others analyse normal sperm parameters. Thus, a worldwide decreasing trend in semen parameter values can be neither confirmed nor rejected.…”
Section: Introductionmentioning
confidence: 99%